LONG-TERM IMPACT OF MACROECONOMIC VARIABLES ON FOREIGN EXCHANGE RESERVES IN THE ORGANIZATION OF ISLAMIC CORPORATION - Heru Wahyudi; Widia Anggi Suripto (Universitas Airlangga, 2023)
One of the factors that influence the country's economy is foreign exchange reserves. This study examines the long-term effect of inflation variables, Gross Domestic Product (GDP), exports, imports, and receipts of remittances in 7 countries of the Organization of Islamic Cooperation. This study uses secondary data panels in 7 countries of the Organization of Islamic Cooperation from 1990 to 2021. The method used in this analysis is the Fully Modified Ordinary Least Square (FMOLS) panel. The results of this study are the variables used are cointegrated in the long run. There are partially negative and significant effects on foreign exchange reserves in 7 countries of the Organization of Islamic Cooperation. GDP and exports have a significant positive effect on foreign exchange reserves. Imports have a negative and insignificant effect on foreign exchange reserves and receipts of remittances have a positive and insignificant effect on foreign exchange reserves in the 7 OIC countries from 1990-2021. This research is expected to contribute to the Cooperation Organization countries related to increasing foreign exchange reserves through macroeconomic control of inflation control, increasing export diversification, increasing export diversification, decreasing imports, and increasing remittances while still paying attention to people in work abroad. It is hoped that the increase in foreign exchange reserves that can improve the organization's economic level can optimize cooperation in Islamic Cooperation, namely to support international peace and security and protect the holy places of Muslims.